Contribution to the Methodology for Determining the Competitiveness of a Domestic Product (on Example of Geotextile) - Ivan Novak (7th International OFEL Conference on Governance, Management and Entrepreneurship: Embracing Diversity in Organisations. April 5th - 6th, 2019, Dubrovnik, Croatia, 2019)
The idea of this paper is to align the business decision-making process with detected product competitiveness characteristics of the domestic company on the domestic market. For this paper was designed "proposal of the operational steps of a simple market and product research methodology", for the existing product in the existing market. These operational steps should be a small contribution for the development of rules and procedures for managing marketing functions in business activities. This is also the practical and theoretical contribution of this paper. The proposal implies the steps outlined and operationally carried out in this paper. Namely, this paper through its structure follows the proposed methodology as an example of the process that companies should pursue. According to literature, for this paper available and explored, there is a room to research the impact of such procedures and rules in order to increase the selling efficiency of products in terms of detected market circumstances and comparative advantages. Therefore, an indicative question was set down for this paper: "How much domestic product is competitive on the domestic market?" This question points out many problems with which are faced underdeveloped but open economies such as Croatia, primarily in order to protect their own production and taking larger domestic market share. Through an example of geotextile, the competitiveness of domestic products was investigated in compare with foreign products by determining certain characteristics that affect purchasing decisions. Hypotheses were set. Hypotheses implies a high quality domestic product (H-1), price as the main purchasing decision maker (H-2) and low awareness of the importance of purchasing domestic products (H-3). The assumption is that the proposed methodology is correlated with hypotheses H1 to H3, for the purpose of determination of market potential of products. An analysis of the Croatian geotextile market was conducted, competitive products were compared and consumer preferences were explored when deciding on purchases. The research results indicate the necessity of applying, even simple, product and market research methodologies. Namely, the analysis of the results showed that the qualitative competitiveness of domestic products in relation to the foreign products is not satisfactory, the price is not the most important deciding factor and the domestic origin of the product as a decision making factor is not important.
Keywords: 650; competitiveness; decision-making; domestic product; geotextile; methodology